Investing in animal health research to alleviate poverty - Perry, Brian D.; Randolph, Thomas F.; McDermott, John J.; Sones, Keith R.; Thornton, Philip K. (International Livestock Research Institute, 2002)
This presentation starts with a discussion on the need of this study and outlines its framework. It then assesses in detail how to attack poverty, and tries to answer the question where do livestock and their diseases fit in? Then it presents the study design and how it is achieved. It then presents a quantitative assessment of poverty, and looks into qualitative approach, poverty indicators, livestock production systems, priority species for the poor along with their objectives and step to achieving them. It then presents an assessment of disease impact with examples. It then examines the distribution of poverty, the association of livestock species with the poor, animal diseases and their impact on the poor, and zoonotic diseases and their impact on the poor. It also presents in detail disease impact ranking. The role of research in alleviating poverty through animal health; research opportunities for the development and adaptation of disease control technologies targeted at the poor and for their delivery adoption and impact; the balance between diseases with the highest impact and the opportunities for research on their better control (a synthesis of research priorities) are other topics of discussion. The paper concludes its discussion with examining issues like generic areas from the field, generic delivery and adoption issues, synthesis of opportunities derived from all sources, and the balance between diseases with the highest impact and the opportunities for research on their better control. The presentation ends with a summary of funding requirements and sources.